2006
DOI: 10.1107/s1744309106046823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the magnesium and chloride ions and shikimate on the structure of shikimate kinase fromMycobacterium tuberculosis

Abstract: PDB References: shikimate kinase-ADPshikimate complex, 2dfn, r2dfnsf; shikimate kinase-MgADP complex, 2dft, r2dftsf.Bacteria, fungi and plants can convert carbohydrate and phosphoenolpyruvate into chorismate, which is the precursor of various aromatic compounds. The seven enzymes of the shikimate pathway are responsible for this conversion. Shikimate kinase (SK) is the fifth enzyme in this pathway and converts shikimate to shikimate-3-phosphate. In this work, the conformational changes that occur on binding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…However, insights into the chemical and kinetic mechanisms of the enzyme have recently been published [83,84] . By contrast, substantially more work has been performed on the fifth and sixth enzymes of the pathway: SK and EPSP [56,57,59,60,69,94] . Two small molecular inhibitors against Helicobacter pylori shikimate kinase have recently been identified through high-throughput screening: 3-methoxy-4-{[2-({2-methoxy-4-[(4-oxo-2-thioxo-1,3-thiazolidin-5-ylidene)methyl]phenoxy}methyl)benzyl]oxy} benzaldehyde and 5-bromo-2-(5-{[1-(3,4-dichlorophenyl)-3,5-dioxo-4-pyrazolidinylidene]methyl}-2-furyl)benzoic acid.…”
Section: Drug Development Based On the Shikimate Pathwaymentioning
confidence: 91%
See 2 more Smart Citations
“…However, insights into the chemical and kinetic mechanisms of the enzyme have recently been published [83,84] . By contrast, substantially more work has been performed on the fifth and sixth enzymes of the pathway: SK and EPSP [56,57,59,60,69,94] . Two small molecular inhibitors against Helicobacter pylori shikimate kinase have recently been identified through high-throughput screening: 3-methoxy-4-{[2-({2-methoxy-4-[(4-oxo-2-thioxo-1,3-thiazolidin-5-ylidene)methyl]phenoxy}methyl)benzyl]oxy} benzaldehyde and 5-bromo-2-(5-{[1-(3,4-dichlorophenyl)-3,5-dioxo-4-pyrazolidinylidene]methyl}-2-furyl)benzoic acid.…”
Section: Drug Development Based On the Shikimate Pathwaymentioning
confidence: 91%
“…For example, although the crystal structure of the E. coli DAHP synthase, the first enzyme of the shikimate pathway, has been known for some time [89] , only recently has the preliminary M. tuberculosis DAHP synthase three-dimensional structure ADP Shikimate Figure 3 . M. tuberculosis shikimate kinase complexed with shikimate and ADP [69] .…”
Section: Drug Development Based On the Shikimate Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…The SB domain is highly conserved and involves a number of charged residues, specifically Arg136, Arg58, Glu61, Asp34, Arg117 and Lys15, and a lipophilic pocket formed by Phe49, Phe57, Pro118, Gly79, Gly80 and Gly81 (in Mt-SK). Circular dichroism [21], fluorescence [22] and structural [20][21][22][23][24] studies suggested that ATP first binds to the enzyme and induces a large movement of the LID domain over the active site. Shikimic acid (6) subsequently binds to the active site and the LID domain closes over the active site and brings Arg110 and Arg117 into the ATP and SB domains, respectively [20].…”
Section: Substrate Recognitionmentioning
confidence: 99%
“…These important features have encouraged diverse research groups to study in detail the substrate binding requirements of this enzyme [20][21][22][23][24][25]. As a result, several crystal structures of SK, mainly from M. tuberculosis, have been reported, either as binary complexes with ATP, ADP or shikimic acid (6) in the active site, or as tertiary complexes with ADP/shikimic acid (6) or ADP/shikimate 3-phosphate (7) [20][21][22][23]. These structures have been an excellent starting point for the structure-based design of inhibitors, which will be discussed below.…”
Section: Targeting Shikimate Kinasementioning
confidence: 99%